Epigenetic Age Acceleration and Hearing: Observations From the Baltimore Longitudinal Study of Aging - Kuo, Pei-Lun; Moore, Ann Zenobia; Lin, Frank R.; Ferrucci, Luigi (Frontiers in Aging Neuroscience, 2021)
Objectives: Age-related hearing loss (ARHL) is highly prevalent among older adults, but the potential mechanisms and predictive markers for ARHL are lacking. Epigenetic age acceleration has been shown to be predictive of many age-associated diseases and mortality. However, the association between epigenetic age acceleration and hearing remains unknown. Our study aims to investigate the relationship between epigenetic age acceleration and audiometric hearing in the Baltimore Longitudinal Study of Aging (BLSA). Methods: Participants with both DNA methylation and audiometric hearing measurements were included. The main independent variables are epigenetic age acceleration measures, including intrinsic epigenetic age acceleration—“IEAA”, Hannum age acceleration—“AgeAccelerationResidualHannum”, PhenoAge acceleration—“AgeAccelPheno”, GrimAge acceleration—“AgeAccelGrim”, and methylation-based pace of aging estimation —“ DunedinPoAm.” The main dependent variable is speech-frequency pure tone average. Linear regression was used to assess the association between epigenetic age acceleration and hearing. Results: Among the 236 participants (52.5% female), after adjusting for age, sex, race, time difference between measurements, cardiovascular factors, and smoking history, the effect sizes were 0.11 (95% CI: [-0.00, 0.23], p=0.054) for Hannum’s clock, 0.08 (95% CI: [-0.03, 0.19], p=0.143) for Horvath’s clock, 0.10 (95% CI: [-0.01, 0.21], p=0.089) for PhenoAge, 0.20 (95% CI: [0.06, 0.33], p=0.004) for GrimAge, and 0.21 (95% CI: [0.09, 0.33], p=0.001) for DunedinPoAm. Discussion: The present study suggests that some epigenetic age acceleration measurements are associated with hearing. Future research is needed to study the potential subclinical cardiovascular causes of hearing and to investigate the longitudinal relationship between DNA methylation and hearing.